Analisis Kontrastif Pasangan Kalimat Transitif-Intransitif Bahasa Indonesia dan Bahasa Jepang - Puspa Mirani Kadir; Inu Isnaeni Sidiq; Cece Sobarna (Badan Pengembangan dan Pembinaan Bahasa, 2023)
In Japanese, the pairs of transitive- intransitive verbs are known as jidoushi/tadoushi (abbreviated as jita). There are approximately 1,256 or 22.6% of the total Japanese verbs inventory. This research aims to affirm Kageyama's (1998) formulation concerning the lexical concept structure (LCS) in transitive-intransitive paired verbs, jidoushi-tadoushi (hereinafter referred to as jita). Through this conceptual structure, jita can be contrastively compared with verbs in Indonesian language, revealing clear similarities and differences, both structurally and semantically. The theories used in this study include Hayatsu's (1995) theory, which reveals the structure and meaning of transitive-intransitive paired verbs; and Kaeyama’s (1998) theory, which proposes the lexical conceptual structure 'Lexical Conceptual Structure' (LCS) providing clarity in classifying Japanese verbs that can form stative/dynamic, possessive/processive, reflexive/non-reflexive, and unintentional/intentional verb pairs. Meanwhile, the transitive-intransitive theory in Indonesian language adopts the theories of Kridalaksana (2005) and Wijana (2021). The data was taken from Japanese sentences in Yoshimoto Banana's novel 'Kitchin' (2005) along with the novel translated into Indonesian, and supplemented by Asahi Shinbun newspaper for vocabulary that is not found in the novel. The research results show that, in Japanese, the transitive verbs form the intransitive verbs; while in Indonesian; intransitive verbs typically derive from transitive verbs. It is proven from the analyzed data, revealing that the semantic functions of possessiveness and intentionality, as well as the meaning of unintentional and intentional actions, associated with transitive verbs affixed with me(N)+kan and intransitive verbs affixed with ber-, closely align with the meanings of jita verb pairs in the Japanese. AbstrakVerba bahasa Jepang memiliki pasangan transitif-intransitif atau yang biasa dikenal dengan jidoushi/tadoushi (jita) itu ada sekitar 1256 buah atau 22,6% dari keseluruhan verbanya. Tujuan penelitian ini merupakan penegasan rumusan Kageyama (1998) terhadap struktur konsep leksikal (LCS) pada verba berpasangan transitif-intransitif jidoushi-tadoushi (selanjutnya disingkat jita). Dengan struktur konsep ini jita dapat diperbandingkan secara kontrastif dengan verba dalam bahasa Indonesia sehingga muncul persamaan dan perbedaan yang jelas, baik secara struktur maupun semantik. Adapun teori yang digunakan dalam penelitian ini yaitu teori Hayatsu (1995) yang mengungkapkan struktur dan makna transitif-intransitif verba berpasangan dan struktur konseptual leksikal ‘Lexical Conceptual Structure’ (LCS) ancangan Kageyama (1998) yang memberikan ketegasan dalam pengelompokan verba berpasangan bahasa Jepang yang dapat membentuk verba statif/dinamis, posesif/prosesif, refleksif/nonreflektif, dan ketidaksengajaan/kesengajaan. Sementara itu, teori transitif-intransitif dalam bahasa Indonesia digunakan teori dari Kridalaksana (2005); Wijana (2021). Teknik pengumpulan data dengan cara menelaah kalimat bahasa Jepang yang terdapat dalam novel ‘Kitchin ‘ karya Yoshimoto Banana (2005) berikut terjemahannya disertai koran Asahi Shinbun untuk kosa-kata yang tidak ada dalam novel tersebut. Hasil penelitian ini pada hal yang khusus terjadi dalam bahasa Jepang adalah adanya proses terbentuknya verba transitif yang berasal dari verba intransitif, sedangkan dalam bahasa Indonesia verba intransitif umumnya terjadi dari transitif. Hal ini terungkap dari data yang telah dianalisis bahwa fungsi semantik possesive dan intentional serta makna kesengajaan/tidak (unintentional and intentional) yang dimiliki verba transitif yang berafiks me(N)+kan dan verba intransitif berafiks ber-, sangat bersesuaian dengan makna verba berpasangan jita dalam bahasa Jepang.